Multidrug resistance, prevalence and phylogenetic analysis of genes encoding class II and III integrons in clinically isolated Escherichia coli - Taha, Manal Mohamed Elhassan; Homeida, Hisham Elraih; Dafalla, Omer Mohammed Elhassan; Abdelwahab, Siddig Ibrahim (Cellular and Molecular Biology, 2018)
The present study was conducted to evaluate the susceptibility, multidrug resistance and genetic characteristics of Escherichia coli (E. coli) strains, isolated from clinical samples from Jazan Hospital, Jazan, Saudi Arabia. A total of 95 samples were recruited from wound, urine, stool and blood. The isolates were assessed for their antibiotic susceptibilities and the presence of class II and III integrons was studied using PCR technique. Integron II-positive PCR products were further confirmed using partial sequencing. Ampicillin (84.2%) was found to be the most resistant antibiotic followed by ciprofloxacin (57.9%), gentamicin (56.8%), nalidixic acid (50.5%), cefotaxim (49.5%), ofloxacin (45.3%), amikacin (26.3%) and imipenem (16.8%), respectively. Seventy-six isolated strains were designated as multidrug resistant (MDR), while non-MDR was found in 19 strains (20.0%). Out of 76 MDR E. coli isolates, 41 (53.9%) were identified as positive for class II and 5 (6.5%) were positive for class III integron. Bioinformatics’ analysis have shown that the sequences of our samples aligned along with many published sequences of integron II. Our findings further strengthen the significance of hospital-based and community E. coli strains on rising the burden of antimicrobial resistance.